Development of Zepeto- and Kinemaster-Based 3D Animation Learning Videos on Fractional Number Material in Class IV SD Negeri 091326 Bahapal Raya - Jessica Stephany Sirait; Nurmayani; Robenhart Tamba; Elvi Mailani; Fahrur Rozi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to produce 3D animated video learning media based on Zepeto and Kinemaster, to determine the feasibility of 3D animated video learning media based on Zepeto and Kinemaster and to find out the effectiveness of 3D animated video learning media based on Zepeto and Kinemaster on Fractional Number Material in Class IV SD Negeri 091326 Bahapal Kingdom. This research and development was carried out using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation) with the research subject being class IV students at SD Negeri 091326 Bahapal Raya. The results of this development research are in the form of appropriate and effective learning media to use. Based on the results of the pre-test and post-test, it was obtained an increase in student learning outcomes with KKM achievement. Before using 3D animation video learning media based on Zepeto and Kinemaster the average student score was 51.05 in the